SYPHILIS PREVALENCE AND ITS CO-INFECTION WITH HBV, HCV, AND HIV AMONG HEALTHY BLOOD DONORS AT A TERTIARY CARE CENTER. : J Peop Univ Med Health Sci. 2025:15(3), 30-35. http://doi.org/10.46536/jpumhs/2025/15.03.655 - Zareen Irshad1, Faiza Zeeshan2, Salma Parveen3, Shahzad Ali Jaskani4, Humaira Ashraf5, Muhammad Anwar6, Yumna Anwar7. (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
However, there is a risk for the recipient of acquiring TTIs, so it is crucial to have data regarding the prevalence of these TTIs and to have strict strategies to reduce their transmission. OBJECTIVE: To determine the prevalence of syphilis and its co-infection with HBV, HCV, and HIV among healthy blood donors. To find out the association of syphilis with different age groups. DESIGN: A descriptive study with non-probability, consecutive sampling. PLACE of study: Blood Bank, Jinnah Postgraduate Medical Centre, Karachi. DURATION OF STUDY: January 2021 to December 2022 METHODOLOGY: All blood donors who fulfilled standard departmental blood donation selection criteria and consented were included in the study. Using an aseptic technique, the serum blood sample was taken from blood donors. Serological tests for HBsAg, Anti-HCV, HIV antigen-antibody combination, and syphilis were analyzed by an automated chemiluminescent microparticle immunoassay (CMIA) method. RESULTS: The study included a total of 48,731 blood donors. The mean age was 29.5±8.56 years (range 18-65). The prevalence of syphilis positivity was seen in 1125(2.3%) cases. According to age groups, it was most prevalent in 18 to 32 years in 638(1.3%), then in 48- 65 years, which was found in 404(0. 8%), whereas it was least prevalent in the middle age group and accounted for 83(0.2%). The co-infection of syphilis with HBV, HCV, and HIV was also reported in 20 (1.8%), 32 (2.8%), and 07 (0.6%) cases, respectively. CONCLUSION: Syphilis was found in 2.3% of healthy blood donors. The study proposes to impose strict measures to control the spread of syphilis and co-infection with other TTIs.